“Apple Blossoms” and “The Apple Tree”: Two Perspectives Typological and Ideological Similarities in Short Stories by Mykhailo Kotsiubynsky and John Galsworthy - Halchuk, Oksana (Respectus Philologicus, 2020)
The article provides comparative analysis of Apple Blossoms by Mykhailo Kotsiubynsky and The Apple Tree by John Galsworthy. Both authors explore human morality in a crisis of confrontation between sensuality and death, the beauty of life and the beauty of art. At the structural level, the works share an element of paratext, novelistic nature, polysemic images-landscapes, and methods of psychologization. Galsworthy engages the antinomy of the city – province, resorts to irony, and combines elements of impressionist writing with the traditions of realistic socio-psychological prose. In contrast, Kotsiubynsky systematically implements the impressionist fragmentary nature of the composition, symbolism of visual and auditory images, in-depth psychoanalysis, and the conventionality of the chronotope.The issues of short stories are diversified and aesthetic – as is distinct for modernist literature – implicitly in Kotsiubynsky’s work, and most explicitly through the connections with the Antiquity and English intertext in Galsworthy’s prose.
Keywords: Mykhailo Kotsiubynsky; John Galsworthy; comparative analysis; Modernism; intertext